Portrait Quality of Life of a Mother Raising a Child with Autism - Alvina Rachma; Lufiana Harnany Utami (International Conference on Sustainable Health Promotion, 2025)
This study aims to explore what life is like for a mother raising a child with autism. A mother’s quality of life in this situation is shaped by four main aspects: physical health, psychological well-being, social relationships, and the environment. The research used a qualitative case study design with one participant—a mother of a 4.5-year-old child with autism. Data were collected through in-depth interviews and direct observation. The results show that the mother experienced many challenges in these aspects, such as feeling physically exhausted from lack of sleep, emotional stress, and financial struggles in paying for her child’s therapy. On the other hand, family support, acceptance of the child’s condition, and a supportive environment—like access to good special school facilities—helped her improve her quality of life. This study is expected to give useful insights for strengthening support systems for mothers raising children with autism so that their lives can become healthier and more balanced.